Analysis of efficiency and reliability of blast-furnace process waste heat recovery systems - Ganzha, A.; Zaiets, O.; Koshelnik, Aleksndr (Полтавська державна аграрна академія; НВП ПП "Технологічний Центр", 2017)
The object of research is a hot blast generating system, which consists of three hot blast stoves with sequential mode of operation. One of the factors that reduce the hot blast stove block efficiency is the existence of losses with the waste gases, the heat of which can be recovered and used for combustion air preheating. In order to improve the efficiency of a hot blast generating system the possibility of using of recuperative heat exchanger for waste heat recovery is observed. The process of initial parameters determining (the required level of combustion air preheating, waste gases temperature and flow rate at the inlet of the heat exchanger) is described. Software based on using of an original mathematical model and used for calculating of the parameters of the waste heat recovery heat exchanger was created. These data provide tools for refined calculation of heat recovery systems based on recuperative heat exchangers. It is shown that the combustion air preheating results in a reduction of the coke oven gas flow rate. The calculations results in building of temperature distribution diagrams that allow to define the areas of corrosion. Such areas in the observed recuperative heat exchanger model appear at temperatures below 26 °C. Thus, the set approaches can be used to refine the calculation of heat-transfer equipment of waste heat recovery systems to improve their reliability, long life, analyze their technical and economic parameters. This will improve the energy efficiency of the hot blast stoves block and reduce the cost of iron production.

Рассмотрена система утилизации теплоты дымовых газов доменных воздухонагревателей для подогрева их воздуха горения. Описаны аспекты определения исходных данных и создание программно-вычислительного комплекса для расчета рекуперативного утилизатора на основе авторской методики. Продемонстрированы результаты расчетов при различных начальных параметрах воздуха и получены температурные диаграммы поверхности теплообмена, на которых можно выявлять области коррозии.
Анализ эффективности и надежности систем утилизации сбросной теплоты доменного производства
Keywords: hot blast stove; heat recovery; доменные воздухонагреватели; продукты сгорания; дымовые газы; утилизация теплоты; рекуператор